Agroecology and sustainable development: reflections in syndemic times. - Silva , Alexandre da (2022)
This work aims to build a reflection on elements inherent to agroecological thinking, from a reality of crisis that has a share in the environmental scope and which is imbricated in issues of development and sustainability. The context of the work develops from the year 2020, which presented a completely new scenario for the humanity of the current generation: a pandemic promoted by the Covid-19 disease. Such intent gains in importance given the scenario presented and the urgency of (re)thinking about the planet we live on and the societies in which we are inserted. To this end, the work is structured, demonstrating the logic of syndemic (synergy between economic, social, political and environmental elements with a pandemic scenario) and a review of the relevance of the concept of risk society; then, he presents the reflections on agroecology in this myriad and, finally, he makes his final remarks stressing the need for a transition to a different path based on principles better able to mitigate or resist future crises - whether pest outbreaks, pandemics, weather disturbances or financial meltdowns; thus building a path of development and sustainability.